EFFECT OF THERMAL AND LIGHT IRRADIATIONS ON OPTICAL PROPERTIES AND SHORT- AND MEDIUM-RANGE ORDER IN ATOMIC STRUCTURE OF AMORPHOUS CHALCOGENIDE FILMS PREPARED BY DIFFERENT METHODS - Sarsembinov, Sh.Sh.; Prikhodko, O.Yu.; Ryaguzov, A.P.; Maksimova, S.Ya.; Ushanov, V.Zh. (Recent Contributions to Physics, 2008)
The changes in optical properties and atomic structure of as-prepared amorphous As2Se3 and As2S3 films upon annealing and light irradiation have been studied. The films were prepared by the methods of thermal evaporation in a vacuum and radio frequency ion plasma sputtering. It was found that after the thermal and light irradiations the optical transmission edge of the films is shifted and there are some changes in atomic film structure. The most essential changes in atomic structure and optical properties as well as a correlation between the changes in the medium-range order of the atomic structure and the optical band gap have been revealed in the TE films7.